2007
DOI: 10.1097/01.tp.0000285265.86954.80
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Reduction After Heart Transplantation With Beta-Blocker Versus the Selective If Channel Antagonist Ivabradine

Abstract: Heart rate reduction with ivabradine is effective and potentially better tolerated than beta-blocker therapy in heart transplant recipients. Although the prognostic role of heart rate after HTX is unknown, ivabradine may offer relevant symptomatic benefit, especially in cases of beta-blocker intolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 21 publications
7
55
0
1
Order By: Relevance
“…A previous study [19] showed that ivabradine, like betablockers, was effective to reduce HR in transplant patients. However, its impact on mortality was not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [19] showed that ivabradine, like betablockers, was effective to reduce HR in transplant patients. However, its impact on mortality was not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Lowering heart rate is therefore one of the most important therapeutic approaches in the treatment of these diseases. Currently used bradycardic drugs including ␤-adrenoceptor antagonists, and some Ca 2ϩ channel antagonists efficiently reduce heart rate, but their use is also limited by adverse reactions or contraindications (44,127). Given the key role of I h /HCN channels in cardiac pacemaking, these channels are very promising pharmacological targets for the development of novel and more specific heart-rate reducing agents (44).…”
Section: A Heart Rate-reducing Agentsmentioning
confidence: 99%
“…Moreover, in heart transplant recipients, sinus tachycardia is rather common as a consequence of graft denervation [4]. Following partial recovery from cardiogenic shock and IABP removal, we aimed at carefully slowing down heart rate with esmolol to improve cardiac function [5].…”
Section: Discussionmentioning
confidence: 99%